2021
DOI: 10.1007/s40520-021-01899-8
|View full text |Cite
|
Sign up to set email alerts
|

Delirium symptoms duration and mortality in SARS-COV2 elderly: results of a multicenter retrospective cohort study

Abstract: Background Since the occurrence of the SARS-COV2 pandemic, there has been an increasing interest in investigating the epidemiology of delirium. Delirium is frequent in SARS-COV2 patients and it is associated with increased mortality; however, no information is available on the association between delirium duration in SARS-COV2 patients and related outcomes. Aims The aim of this study is to investigate the association between the duration of delirium symptoms and in-hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…We found that a combination of high-risk NSS and the absence of low-risk NSS, increased the risk of in-hospital death nearly 8-fold in patients with SARS-CoV-2 infection. It was previously noted that isolated neurological symptoms, such as decreased level of consciousness [ 32 ], delirium [ 33 ], or stroke symptoms [ 34 ], were associated with increased mortality in COVID-19 patients. The latest literature review showed that any neurological manifestation of SARS-CoV-2 infection was correlated with a higher mortality rate [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that a combination of high-risk NSS and the absence of low-risk NSS, increased the risk of in-hospital death nearly 8-fold in patients with SARS-CoV-2 infection. It was previously noted that isolated neurological symptoms, such as decreased level of consciousness [ 32 ], delirium [ 33 ], or stroke symptoms [ 34 ], were associated with increased mortality in COVID-19 patients. The latest literature review showed that any neurological manifestation of SARS-CoV-2 infection was correlated with a higher mortality rate [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among other variables such as comorbidities and severity of the underlying disease, the duration of delirium is associated with adverse consequences [ 22 22 ]. Morandi et al described a 10% increase in in-hospital mortality among older SARS-CoV2 patients with each day with delirium [ 21 ]. Therefore, non-pharmacological delirium interventions play a vital role in delirium management.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-acute care, often defined as care for older patients with decompensated well-known chronic conditions, represent expanding healthcare services to face the increase of comorbidity and complex healthcare and social needs, and might be included into the broad category of intermediate care resources [ 12 , 18 ]. During the pandemic, these services have been predisposed to care for COVID-19 older patients as a complement to the insufficient acute hospital capacity for selected acute patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review reported a high prevalence and incidence of delirium in older patients with COVID-19 in acutely hospitalized patients [ 8 ]. However, only a few studies were conducted in rehabilitation and nursing homes [ 4 , 5 ]. Moreover, several studies have focused on the association between delirium and mortality in COVID-19, but little is known about the relationship between delirium and functional performances [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation